DAMPAK BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN MELALUI TINGKAT KEDISIPLINAN SEBAGAI VARIABEL MEDIASI - Nafisah, Jauharotun; Cahyadi, Nur (Universitas Sarjanawiyata Tamansiswa, 2024)
The research titled “The Impact of Organizational Culture on Employee Performance through Discipline Level as a Mediating Variable” aims to identify and analyze how organizational culture influences employee performance, considering discipline as a factor that can strengthen this relationship. This research uses explanatory research methods with a quantitative approach. This research was conducted at PT. XYZ, utilizing a Likert scale for data collection. The population of this research is all employees of PT XYZ with data collection in the form of surveys and questionnaires. The research results show that organizational culture has a significant influence on employee discipline, with a very high influence value of 0.977. These findings confirm that organizational culture plays an important role in shaping employee behavior in an organization. This research provides empirical evidence that developing an organizational culture that supports discipline is an important strategy for improving employee performance.. A work environment that values discipline and commitment will encourage employees to align their behavior with the organization's values, ultimately contributing to increased productivity and overall work quality.